1974
DOI: 10.1192/bjp.125.4.406
|View full text |Cite
|
Sign up to set email alerts
|

How Depressives View the Significance of Life Events

Abstract: The role of a broad range of life events, especially those viewed as stressful, in the genesis of somatic illnesses or psychiatric disturbances is a subject of considerable interest. Recently attempts have been made to develop quantitative measures of life events and to explore the relationship between the ‘amount’ of life events and/or stress and illness in a general population (Rahe et al., 1968; Rahe et al., 1970): for example, The Social Readjustment Rating Questionnaire (SRRQ) (Holmes and Rahe, 1967). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Brown & Harris, 1978;Grant et al, 1976;Lennon, Dohrenwend, Zautra, & Marbach, 1990;Raphael & Cloitre, 1994;Schless, Schwartz, Goetz, & Mendels, 1974;Theorell, 1974). For example, Theorell investigated two sets of ratings-by samples of patients with neurotic diagnoses, patients who had myocardial infarctions (MI) and controls-of items on a revised version of the SRE.…”
Section: Respondent Appraisals Of Stressfulnessmentioning
confidence: 99%
“…Brown & Harris, 1978;Grant et al, 1976;Lennon, Dohrenwend, Zautra, & Marbach, 1990;Raphael & Cloitre, 1994;Schless, Schwartz, Goetz, & Mendels, 1974;Theorell, 1974). For example, Theorell investigated two sets of ratings-by samples of patients with neurotic diagnoses, patients who had myocardial infarctions (MI) and controls-of items on a revised version of the SRE.…”
Section: Respondent Appraisals Of Stressfulnessmentioning
confidence: 99%
“…Persons suffering from mental illness appear more vulnerable to interpersonal problems and irritability (Schless, et al 1974;Tweed 1993). Many recipients obtain employment or slots in job training programs only to lose them due to confrontations with coworkers and supervisors, lateness, and similar violations of workplace norms.…”
Section: Department Of Health and Human Services 1992) In Dramatic Fmentioning
confidence: 99%
“…Depressed patients tend to recall more negative and stressful events (Clark and Teasdale, 1982) and to rate these events as more salient and unpleasant (Schless et al, 1974). It has been suggested that physiological changes, such as high cortisol levels and increased 5-HT receptor density, observed in many patients with depression might be linked to these negative cognitive biases (Lopez et al, 1997;Barden et al, 1995).…”
Section: Introductionmentioning
confidence: 99%